William Blake and the Bible: Reading and Writing the Law - Michael Farrell (University of Edinburgh, 2006)
Samuel Beckett notes an etymological connection between the origin of the word law and the act of reading in the evolution of the Latin word lex (Beckett 11). The word lex originally meant a crop of acorns and its correlative verb legere meant to gather (acorns). Gradually, lex came to mean a gathering of peoples into an assembly - a political or legal assembly - and hence law; and the verblegere came to mean a gathering of letters into a word, to read. In the light of the notion that the Bible promotes unbounded reading, it is necessary to consider to what extent the activity of reading and interpretation is bound by law and convention.